2001
DOI: 10.1039/b103280c
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative 3-dimensional profiling of channel networks within transparent ‘lab-on-a-chip’ microreactors using a digital imaging method

Abstract: We have developed a method for the quantitative 3-dimensional profiling of micron sized channel networks within optically transparent "lab-on-a-chip" microreactor devices. The method involves capturing digitised microscope images of the channel network filled with an optically absorbing dye. The microscope is operated in transmission mode using light filtered through a narrow bandpass filter with a maximum transmission wavelength matching the wavelength of the absorbance maximum of the dye solution. Digitised … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 16 publications
0
31
0
Order By: Relevance
“…The final device was generated in glass using standard photolithography and wet-etching techniques. 4 Access holes and a central chamber (diameter 3 mm) were drilled in the top plate and was then thermally bonded with the etched bottom plate in a furnace at 590°C for 3 h. The channel network was etched into the bottom 1-mm glass layer to produce channels of 190-lm width and 70-lm depth, which diverged into two channels as shown in Fig. 1.…”
Section: Design and Microfabrication Of The Microfluidic Devicementioning
confidence: 99%
See 1 more Smart Citation
“…The final device was generated in glass using standard photolithography and wet-etching techniques. 4 Access holes and a central chamber (diameter 3 mm) were drilled in the top plate and was then thermally bonded with the etched bottom plate in a furnace at 590°C for 3 h. The channel network was etched into the bottom 1-mm glass layer to produce channels of 190-lm width and 70-lm depth, which diverged into two channels as shown in Fig. 1.…”
Section: Design and Microfabrication Of The Microfluidic Devicementioning
confidence: 99%
“…4,23 AutoCAD LT software, a computer-assisted design package, was used to design the microdevice from which a photomask was generated. The final device was generated in glass using standard photolithography and wet-etching techniques.…”
Section: Design and Microfabrication Of The Microfluidic Devicementioning
confidence: 99%
“…These disadvantages can be overcome by using a newly-developed method based on digital microscopic imaging of a dye solution-®lled channel network. 30 As shown in Fig. 4, the chip is mounted on a transmission microscope operating with monochromatic light at a wavelength corresponding to the maximum absorbance of a dye solution within the channel network.…”
Section: Determination Of the 3d Dimensions Of The Channel Networkmentioning
confidence: 99%
“…It was observed that the cross sectional shape of the channel etched by powder blasting consisted of a trapezoidal shape in which the bottom of the channel was slightly rounded. This shape was markedly different from the cross sectional shape obtained for a channel produced by isotropic wet etching of glass which consists of a rectangle flanked by quarter circles [14]. By fitting the channel profile (Fig.…”
Section: Microchannel Profilingmentioning
confidence: 99%
“…To determine the average liquid linear velocity in the channel, it was necessary to profile the channel cross section. An optical microscope absorbance imaging technique [14] of the channel network filled with dye solution was used to obtain the quantitative 3-D profile of the T-junction region (see Fig. 2).…”
Section: Microchannel Profilingmentioning
confidence: 99%